Associations of Retinal Microvascular Density and Fractal Dimension with Glaucoma: A Prospective Study from UK Biobank - Qi Chen, MD; Suyu Miao, MD; Yuzhe Jiang, MD; Danli Shi, MD, PhD; Weiyun You, MD; Lin Liu, MD, PhD; Mayinuer Yusufu, MTI; Yufan Chen, MD; Ruobing Wang, MD, PhD (Ophthalmology Science)
Objective: To explore the association between retinal microvascular parameters and glaucoma. Design: Prospective study. Subjects: The UK Biobank subjects with fundus images and without a history of glaucoma. Methods: We employed the Retina-based Microvascular Health Assessment System to utilize the noninvasive nature of fundus photography and quantify retinal microvascular parameters including retinal vascular skeleton density (VSD) and fractal dimension (FD). We also utilized propensity score matching (PSM) to pair individuals with glaucoma and healthy controls. Propensity score matching was implemented via a logistic regression model with a caliper of 0.1 and a matching ratio of 1:4 no replacements. We conducted univariable Cox regression analyses to study the association between retinal microvascular parameters and incident glaucoma, in both continuous and quartile forms. Main Outcome Measure: Vascular skeleton density, FD, and glaucoma. Results: In a study of 41 632 participants without prior glaucoma, 482 cases of glaucoma were recorded during a median follow-up of 11.0 years. In the Cox proportional hazards regression model post-PSM, we found that incident glaucoma has significant negative associations with arteriolar VSD (hazard ratio [HR] = 0.24, 95% confidence interval [CI] 0.11–0.52, P < 0.001), venular VSD (HR = 0.34, 95% CI 0.15–0.74, P = 0.007), arteriolar FD (HR = 0.24, 95% CI 0.10–0.60, P = 0.002), and venular FD (HR = 0.31, 95% CI 0.12–0.85, P = 0.022). Subgroup analysis using covariates revealed that individuals aged ≥60 years, nonsmokers, moderate alcohol consumers, and those with hypertension and myopia exhibited P values <0.05 consistently prematching and postmatching, differing from other subgroups within this covariate. Conclusions: Our study found that reduced retinal VSD and lower FD are linked to elevated glaucoma risk. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.